2020
DOI: 10.3390/jcm9061958
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Trigger Point Dry Needling Safety by Ultrasound Skin-to-Rib Measurement: An inter-Rater Reliability Study

Abstract: Dry needling (DN) is a minimally invasive treatment technique widely used by physical therapists to treat myofascial trigger points (MTrP). Even if its safety has been commonly declared and the majority of adverse events are considered mild, serious adverse events cannot be excluded and DN treatments of several trunk muscles can potentially result in pneumothorax. Ultrasound imaging (US) skin-to-rib measurement could ensure the safety of this treatment procedure. Therefore, the aim of this study was to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Although dry needling could be considered a safe treatment if properly applied, potential risks associated with its application on each body area where it is applied should be taken into account. In fact, recent studies have proposed different positions [ 63 ] or the use of echography [ 64 ] for improving the safety of dry needling application.…”
Section: Discussionmentioning
confidence: 99%
“…Although dry needling could be considered a safe treatment if properly applied, potential risks associated with its application on each body area where it is applied should be taken into account. In fact, recent studies have proposed different positions [ 63 ] or the use of echography [ 64 ] for improving the safety of dry needling application.…”
Section: Discussionmentioning
confidence: 99%
“…18 For ultrasound imaging, participants were in prone with their arms in the abduction of 90° and elbows flexed. The assessment point was selected following the procedure as described by Folli et al 13 which has been found to be highly reliable. Firstly, the spinous process and the inferior angle of the scapula was identified by manual palpation, and the half distance between these points was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…As a conclusion of their study, they recommended the use of ultrasound evaluation during or before dry needling to ensure the correct needle length. Folli et al recently reported, as assessed with ultrasound imaging, a mean thickness of the major rhomboid muscle of 16.3 mm (males muscle thickness: 25.4 mm; women muscle thickness: 20.4 mm) 13 . However, they routinely use of ultrasound in clinical practice is not always possible because of its high economic costs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is literature that also strongly recommends its use not only as an evaluation tool due to its low cost, safety and portability, but also because of the possibility of obtaining quantitative measurements of tissue texture (thickness, cross-sectional areas or perimeters) and as a guide for invasive interventions such as dry needling or percutaneous electrolysis in anatomical regions of high risk due to space conflict [10][11][12].…”
Section: Introductionmentioning
confidence: 99%